Paul Feyerabend’s Epistemological Anarchism and Its Relevance to the Methodology of Religious Studies - Alfiyan Chasanul Muna; Muhammad Rikza Muqtada (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
The dominance of rigid textual and monolithic methodological approaches in religious studies has increasingly limited the scope of critical and contextual inquiry. This article examines the relevance of Paul Feyerabend’s epistemological anarchism as an alternative framework for enriching the methodology of religious sciences, particularly Islamic studies. Employing a qualitative library-based approach, the study analyzes Feyerabend’s major works through conceptual and content analysis, alongside relevant secondary literature in the philosophy of science and religious studies. The findings demonstrate that Feyerabend’s rejection of a single, universal scientific method—articulated through principles such as “anything goes,” counterinduction, theory proliferation, and incommensurability—offers a productive challenge to methodological rigidity in religious scholarship. His emphasis on methodological pluralism opens space for more inclusive, dynamic, and context-sensitive approaches to theological inquiry and Qur’anic interpretation. The study argues that integrating Feyerabend’s epistemological insights enables religious studies to move beyond methodological absolutism by incorporating sociological, historical, and contextual analyses without undermining the normative role of religious texts. In conclusion, Feyerabend’s epistemological anarchism contributes conceptually to the development of a more adaptive and dialogical paradigm in religious sciences, allowing religious knowledge to engage more effectively with contemporary social realities.